Analisis Anggaran Penjualan UMKM Sabana Fried Chicken Cabang Cikarang - Purwanti, Purwanti; Wicaksono, Agung; Rahayu, Muhamad Naufal; Oktaviani, Tia; Salma, Nabila; Prawira, Muhammad Rivaldo; Nurbaeti, Siti Al'fiah; Saputri, Adelliya Agil; Nanda, Diah Putri Elind; Manapa, Oktaviana Deby; Saputra, Fendi Angga (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the sales forecasting of Sabana Fried Chicken Cikarang Branch. This research uses descriptive qualitative research. The data sources that researchers use are primary data and secondary data. Primary data in the form of interview results with the owner of Sabana Fried Chicken Cikarang Branch. Secondary data in the form of sales data. The data collection techniques that researchers use are documentation, interviews and literature studies. In forecasting sales, researchers use statistical methods of trend analysis, namely using the semi average method, trend moment and least square method.